2017
DOI: 10.1021/acs.langmuir.7b02942
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Gold Nanorod Synthesis with Nanomolar Concentrations of Poly(vinylpyrrolidone)

Abstract: A novel modification for the seedless synthesis of gold nanorods (AuNRs) has been developed. Nanomolar concentrations of 10 kDa poly(vinylpyrrolidone) (PVP) can be introduced to a growth solution containing 25, 50, or 100 mM cetyltrimethylammonium bromide (CTAB) to significantly reduce the dimensions of AuNRs. We found that PVP accelerates the growth rate of AuNRs by more than two times that of nanorods grown in 50 and 100 mM CTAB solutions. Additionally, there is a time-dependent effect of adding PVP to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 64 publications
4
38
0
Order By: Relevance
“…In our previous study, we evaluated the effect of 10 kDa PVP (10PVP) during AuNRs growth for the seedless method with different CTAB concentrations. [30] Based on those results, we decided to perform experiments with growth solutions that contain 100 mM CTAB and exhibit a blue shift of the LSPR band upon the addition of polymer. In the present work, the effect of PVP molecular weight was assessed on the dimensions, aspect ratio and shape yield of AuNRs by the seedless and seedmediated methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we evaluated the effect of 10 kDa PVP (10PVP) during AuNRs growth for the seedless method with different CTAB concentrations. [30] Based on those results, we decided to perform experiments with growth solutions that contain 100 mM CTAB and exhibit a blue shift of the LSPR band upon the addition of polymer. In the present work, the effect of PVP molecular weight was assessed on the dimensions, aspect ratio and shape yield of AuNRs by the seedless and seedmediated methods.…”
Section: Resultsmentioning
confidence: 99%
“…The LSPR band and absorbance as a function of reaction time are shown in Figure 2. After the growth kinetics was compared to the control and the AuNRs solution with 10PVP, [30] it was found that the presence of high molecular weight of PVP accelerates 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 the nanorods growth even more. The nanorods reached a maximum LSPR band 30 and 60 min earlier for 55PVP and 360PVP, respectively (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still severall imitations associated with this method, as it only produces nanorods in milligramq uantities with 15-20 %A u I to Au 0 conversion [28] and the size, aspect ratio, and longitudinal plasmon band (LPB) positiono ft he AuNRs vary from trial to trial.W er eported the use of hydroquinonea sa reducinga genta so pposed to ascorbic acid (AA), and this resultedi nn ear-quantitative conversiono fA u I into Au 0 . [29,30] Directs cale-upo fa ll the components in an equivalent molar ratio to produce ah igherq uantity of AuNRsi sn ot feasible in research laboratory,a si tr equires several liters of growth solution to produce af ew milligrams of AuNRs. Therefore, a methodb yw hich gram quantities of monodisperse AuNRsc an be generated in one batch is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Since this first contribution, a large number of papers based on the seedless protocol have been published, in order to increase the efficiency of AuNR synthesis, enhance their stability, modulate the aspect ratio, eliminate or decrease the CTAB concentration (see recent reviews [ 32 , 35 ]). Zubarev and colleagues [ 36 ] demonstrated that a well-known additive as poly(vinylpyrrolidone (PVP), extensively employed as stabilizing and reducing agent for many kind of metal nanoparticles, could be efficiently used to reduce the AuNR size in a seedless protocol. For the first time, PVP added in very low concentrations with respect to Au 3+ , was used to control the shape growth of gold nanorods in the presence of CTAB, acting as a stabilizing and not as a reducing agent.…”
Section: Synthesismentioning
confidence: 99%